Survey of medical center employees’ willingness and availability to donate blood in support of a civilian warm fresh whole blood program - Hughes, MD, Joy D.; Hernandez, MD, Matthew C.; Jenkins, MD, Donald H.; Rivera, MD, FACS, Mariela; Sawyer, MD, FACS, Mark D.; Kreuter, MD, Justin D.; Stubbs, MD, James R.; Zielinski, MD, FACS, Martin D. (American Journal of Disaster Medicine, 2019)
Objectives: In military settings, utilizing warm fresh whole blood (WFWB) was associated with reduced mortality; however, there are multiple challenges for administering WFWB to civilians. The authors aimed to determine barriers to hospital employees emergently donating to civilian WFWB programs. Methods: We surveyed hospital employee willingness to donate emergently, familiarity with blood donation, and queried baseline demographics. The electronic survey was disseminated to a random sample of employees. Descriptive and univariate analyses were performed. Results: Three thousand surveys were sent; 883 were returned (28 percent). The majority of respondents were female (n = 630, 71 percent). Respondent familiarity with WFWB donation included very/somewhat familiar (n = 381, 43 percent) and somewhat-not/notat- all familiar (n = 356, 40 percent). Most were definitely or somewhat willing to emergently donate (n = 660, 75 percent). Four hundred and sixty would drive from home to donate (52 percent). The majority worked day-time shifts (n = 754, 85 percent). In regards to donation history, 366 (41 percent) had donated blood more than ten times, but 138 (16 percent) had never donated. Barriers to emergent donation were identified (55 percent), with the most common being childcare responsibilities (n = 242; 27 percent). Conclusions: Hospital employees are willing to donate WFWB emergently, but program implementation must address donor availability and logistical barriers. Future research should assess feasibility of a civilian WFWB program by determining regulatory challenges, development of a quality system for emergency donations, assessment of optimal workforce structure, potential impact to the general blood inventory, as well as patient and community perspectives regarding untested blood units.